Posttraumatic Growth And Psychosocial, Cancer And Treatment Related Factors In Head And Neck Cancer: Assessing Their Associations In A Cross-Sectional Study - Hamdan, Nur Amirah (2022)
This cross-sectional study aimed to translate and validate the Fear of Progression Questionnaire-Short Form (FoP-Q-SF) and Cancer Treatment Satisfaction Questionnaire (CTSQ) into Malay (phase 1 of the study) and to determine the associations between unmet supportive needs, fear of cancer progression, healthrelated quality of life, expectation and satisfaction with cancer therapy, and posttraumatic growth (PTG) among a group of head and neck cancer (HNC) patients (phase 2 of the study). In phase 1, 200 participants of various types of cancer were administered with the drafted Malay versions of FoP-Q-SF (FoP-Q-SF-M) and CTSQ (CTSQ-M). The reliability and validity for both of them were assessed. In phase 2, 200 HNC participants were administered with the Posttraumatic Growth Inventory-Short Form (PTGI-SF), European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-H&N35 (EORTC QLQ-H & N35), Fear of Progression Questionnaire-Short Form (FoP-Q-SF), Cancer Treatment Satisfaction Questionnaire (CTSQ) and 34-item Supportive Care Needs Survey- Short Form (SCNS-SF34). The associations between each one of them and PTG were determined by general multivariate regression model with bootstrapping with 2000 replications.